The renewable energy and energy efficiency potential of Waitakere City : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Technology in Energy Management at Massey University - Grooby, Lloyd D (Massey University, 2005)
Electricity restrictions and blackouts have occurred in Waitakere City in the past and are likely to occur again in the future unless the city can become more self reliant by meeting, at least in part, the increasing energy requirements for what is one of the fastest growing cities in New Zealand. In this study the potentials for energy conservation, energy efficiency and renewable energy resources have been broadly quantified and assessed using desktop analysis of publicly available data for stationary final use energy systems (i.e. excluding transportation) within the geographical area of Waitakere City and adjoining waters. It was found that energy efficiency and energy conservation measures can consistently and predictably achieve overall energy savings and reduce daily and seasonal peak demand. The best renewable energy resource potential exists with solar and geothermal for heating applications and wave, offshore and inshore wind and tidal currents for electricity generation. There is very limited potential for hydro and bioenergy systems beyond what already exists. PV solar and land based wind power generation are currently only feasible for limited off-grid applications. This scoping study confirms the achievability of the vision expressed in Waitakere City Council's "Long Term Council Community Plan" (LTCCP) that by 2020 " Waitakere City will be an energy cell, not an energy sink. Air quality supports good health". A range of flagship projects have been identified to progress the achievement of this vision. Waitakere City Council can use this report as part of the development of a comprehensive energy management plan.
Keywords: New Zealand -- Waitakere; Power resources; Renewable energy sources; Energy conservation